The Status of Educational Science in Italy - Bertolini , Piro (Swiss Journal of Educational Research, 2000)
This contribution first discusses the definition of educational science, which in Italy expresses two manifestations: on one hand, in the sense of human science (psychology, sociology, psychoanalysis, etc.) provided that they explicitly apply to educational phenomenon; on the other hand, in the sense of the specific branches of general pedagogy (historical pedagogy, didactics, specialized pedagogy, experimental pedagogy, adult pedagogy, etc.). On this basis, the development of educational science after the Second World War is examined, particularly those factors that formed their orientation: first, the social needs established outside of school, and second, the emergence of a real interest in the training of the teachers. Especially interesting is the striving for autonomy of the field of didactics, which demands its own epistemological status and its own research methods.